2023
DOI: 10.3390/ph16081158
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the In Vitro Toxicity Profile of Psychedelic 2C Phenethylamines and Their N-Benzylphenethylamine (NBOMe) Analogues

Abstract: Mescaline derivative (2C phenethylamines) drugs have been modified by the introduction of a N-2-methoxybenzyl group to originate a new series of compounds with recognized and potent psychedelic effects, the NBOMe-drugs. Although they are prevalent in unregulated drug markets, their toxicity profile is still poorly understood, despite several reports highlighting cases of acute intoxication, with brain and liver toxicity. Thus, in this study, mescaline, 2C-N (insertion of a nitro in the para position of the 2C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…Similar results were described for other NPS, including piperazines (BZP, TFMPP, MeOPP, and MDBP) and phenethylamines (mescaline, 2C-B, 2C-N, mescaline-NBOMe, 25B-NBOMe, and 25C-NBOMe). In agreement with our results, and using the same in vitro model, both studies showed a significant decrease in the tGSH content with no ROS production [21,63].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Similar results were described for other NPS, including piperazines (BZP, TFMPP, MeOPP, and MDBP) and phenethylamines (mescaline, 2C-B, 2C-N, mescaline-NBOMe, 25B-NBOMe, and 25C-NBOMe). In agreement with our results, and using the same in vitro model, both studies showed a significant decrease in the tGSH content with no ROS production [21,63].…”
Section: Discussionsupporting
confidence: 92%
“…We observed that after 24 h of exposure, all the tested drugs (EC 20 and EC 50 ) induced a significant mitochondrial membrane depolarization s and decreased the intracellular ATP levels (Figures 6 and 7), evidencing mitochondrial impairment. Similar results have been reported for other drugs [50,51], including drugs from the 2C and NBOMe families [21].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…4-Bromo-2,5-dimethoxyphenethylamine (2C-B) and all psychoactive compounds tested in this study were prepared following synthetic procedures published by our group [22,23]. 2C-B was prepared by a straightforward synthetic route.…”
Section: Methodsmentioning
confidence: 99%